What are natural antisense transcripts good for? - Werner, Andreas (Biochem Soc Trans, 2010)
NATs (natural antisense transcripts) are important regulators of eukaryotic gene expression. Interference between the expression of protein-coding sense transcripts and the corresponding NAT is well documented. In the present review, we focus on an additional, higher-order role of NATs that is currently emerging. The recent discovery of endogenous siRNAs (short interfering RNAs), as well as NAT-induced transcriptional gene silencing, are key to the proposed novel function of NATs.